Speciation and desulphurisation of sulphur forms in coals and derivatives and petroleum residues / Khudzir Ismail, Mohd Lias Kamal and Mohd Azlan Mohd Ishak - Ismail, Khudzir; Kamal, Mohd Lias; Mohd Ishak, Mohd Azlan (2001)
Combustion of coals to produce electricity has created environmental problems, one of which is sulphur which is converted to SO2 and SO3 gases. In order to produce a "clean coal", the pretreatment processes of sulphur removal from coal have to be effective to remove the inorganic (pyrite) and organic sulphur forms (thiolic, sulphidic and thiophenic). High pressure Temperature-Programmed Reduction (TPR) has been used for specifying the distribution of organic sulphur forms in both pyrite-free Malaysian (Mukah Balingian) and Indonesian coals (Banjarmasin Hj. Ali-Aliansar and Banjarmasin Coal A). The results obtained thus far, indicate that ca. 95% and 75% of sulphidic functionalities are present in Mukah Balingian (MB) and Banjarmasin Coal A (BMA), respectively, with 70%) thiophenic forms are present in Banjarmasin Hj. Ali- Aliansar (BMHAA).